Additional costs in air cargo service and competitiveness of foreign trade enterprises in Metropolitan Lima - Tito Huamaní, Pedro Leonardo (2017)
This research aims to reveal the existence of additional cost in air cargo services affecting the competitiveness of foreign trade enterprises in metropolitan Lima. The investigation reached a descriptive and correlational level, based on surveys of a sample of 119 individuals out of a population of 300 heads of foreign trade in Metropolitan Lima, who work in these businesses. The research leads us to conclude that there are serious differences in the peruvian model of services to the airfreight, which cause the service receiver is not directly involved in negotiating the conditions of all the service, because peruvian law does not define the carrier’s liability to the point of delivery of the goods to the owner of the cargo, generating additional costs in service to the airfreight which influences the competitiveness of foreign trade enterprises in Metropolitan Lima, as they generate conditions of inequality trade relations between the companies that own the cargo (exporters and importers) and service providers (airline, ramp operators and storage terminals).